Effects of size and feeding on the oxygen consumption of Nylon Shell , Paphia undulata (Born.). (Mollusca, Pelecypoda Veneridae). - Valasote, Sweet Cardel P. (2001.)
The effects of size and feeding on the oxygen consumption of the clam P. undulata were studied. Oxygen consumption rate at two different nutritional conditions (Fed and Unfed) with three different size classes each (Small, Medium and Large with shell length ranges 50-59 mm, 60-69 mm and 70-79 mm respectively) were measured. For the fed nutritional status, clams were fed with Chaetoceros gracilis at 60 000-cell ml-1. One individual for each size class was placed in closed respirometer system, which consists of a transparent flexiglass chamber equipped with a YSItmDO meter. Oxygen consumption was measured every minute until DO held a constant reading after three consecutive readings. Oxygen consumption rate (slope) by size class by nutritional status was determined using the regression analysis. Results showed that the smallest size class of the unfed nutritional status had the highest mean oxygen consumption rate (0.0190 mg/L) while the smallest size class of the fed nutritional status showed the lowest mean oxygen consumption rate (0.0111 mg/L). The oxygen consumption rate of P. undulata differed between two nutritional status (p=0.983) but not between size classes (p=0.0068).
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Nylon Shell